A new pro-thrombotic mechanism of neutrophil extracellular traps in antiphospholipid syndrome: impact on activated protein C resistance. (16th November 2021) - Foret, Thomas; Dufrost, Virginie; Salomon du Mont, Lucie; Costa, Patricia; Lakomy, Cecile; Lagrange, Jeremy; Lacolley, Patrick; Regnault, Veronique; Zuily, Stephane; Wahl, Denis
Abstract: Objectives: In APS, precise evaluation of thrombotic risk is a major challenge. Different players, such as activated protein C (APC) resistance or neutrophil extracellular traps (NETs) contribute to the risk of thrombosis. Nevertheless, no study has investigated the interaction between these actors. The main objective of this study was to investigate the relation between NETs and APC resistance. Methods: We designed a cross-sectional study including APS/antiphospholipid antibodies (aPL) patients and patients with autoimmune diseases (AID). We performed thrombin generation tests without and with APC to determine APC resistance. To evaluate circulating NETs, we measured plasma levels of MPO-DNA complexes and cell-free DNA with ELISA. Results: We recruited 117 patients with definite APS/aPL or AID. We found a positive correlation between NETs and APC resistance, in APS patients and specifically in patients with high thrombotic risk, displaying LA or positivity of all three aPL tests (triple+), or anti-domain I IgG (aDI+). All these patient subgroups had increased NETs concentrations and APC resistance. As the risk profile for thrombosis increased, the relationship between NETs and APC resistance was stronger. Conclusion: We have shown that NETs participate in the hypercoagulable state of APS patients by contributing to APC resistance, in particular in high-risk patients. In these most at-risk patients, a targeted action on NETs could reduce APC resistance and constitute a new therapeutic approach in the treatment of APS patients in addition to antithrombotic therapy.